Inovasi Pemanfaatan Limbah sebagai Sarana Pertanian - Jusuf Leiwakabessy; Sherly Lewerissa; Amon Manik; Salsabilla Syarifa La Unga; Irensia K. Nurue; Haganta Br. Tarigan (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2026)
Agricultural and household waste management remains a major issue in rural areas, including Namasina Village, Kota Masohi District, Central Maluku Regency. A large amount of organic waste is disposed of without proper processing, causing environmental pollution, even though it has great potential to be converted into liquid organic fertilizer (LOF) that is eco-friendly and economically valuable. This study aims to increase community knowledge about organic waste management, promote sustainable agricultural innovation, and reduce dependence on chemical fertilizers. The implementation method involves socialization activities and hands-on practice of making LOF using cow manure, brown sugar, EM4, and water, which are fermented for 7–14 days. The results show high enthusiasm among the community in participating in the training and understanding the benefits of LOF in improving soil fertility and reducing production costs. Furthermore, the activity continued with chili planting practices using the homemade organic fertilizer. This program demonstrates that the utilization of livestock and household waste can serve as an effective solution to support sustainable agriculture, increase environmental awareness, and empower the community toward self-sufficiency.